A Critical Evaluation of the National Environmental Management Act (NEMA) Section 24G: Retrospective Environmental Authorisation - Du Toit, Jessica (Stellenbosch : Stellenbosch University, 2016)
Thesis (MPA)--Stellenbosch University, 2016.